Sociodemographic Characteristics Associated with Contacts to Emergency Medical Services and Out-of-Hours Primary Care: An Observational Study of 2.3 Million Citizens - Søvsø MB; Bech BH; Christensen HC; Huibers L; Christensen EF; Christensen MB (Clinical Epidemiology, 2020)
Morten Breinholt Søvsø,1,2 Bodil Hammer Bech,3 Helle Collatz Christensen,4 Linda Huibers,2 Erika Frischknecht Christensen,1 Morten Bondo Christensen2 1Centre for Prehospital and Emergency Research, Aalborg University and Aalborg University Hospital, Aalborg, Denmark; 2Research Unit for General Practice, Aarhus, Denmark; 3Department of Public Health, Research Unit for Epidemiology, Aarhus University, Aarhus, Denmark; 4Emergency Medical Services, Copenhagen, University of Copenhagen, Copenhagen, DenmarkCorrespondence: Morten Breinholt SøvsøCentre for Prehospital and Emergency Research, Aalborg University and Aalborg University Hospital, Søndre Skovvej 15, Aalborg 9000, DenmarkTel +45 9764 4446Email morten.soevsoe@rn.dkBackground: Out-of-hours (OOH) health care services are often divided into emergency medical services (EMS) and OOH primary care (OOH-PC). EMS and many OOH-PC use telephone triage, yet the patient still makes the initial choice of contacting a service and which service. Sociodemographic characteristics are associated with help-seeking. Yet, differences in characteristics for EMS and OOH-PC patients have not been investigated in any large-scale cohort studies. Such knowledge may contribute to organizing OOH services to match patient needs. Thus, in this study we aimed to explore which sociodemographic patient characteristics were associated with utilizing OOH health care and to explore which sociodemographic characteristics were associated with EMS or OOH-PC contact.Methods: A population-based observational cohort study of inhabitants in two regions (North Denmark Region and Capital Region of Copenhagen) with or without contact to OOH services during 2016 was conducted. Associations between sociodemographic characteristics and OOH contacts (and EMS versus OOH-PC contact) were evaluated by regression analyses.Results: We identified 619,857 patients with OOH contact. Female sex (IRR=1.16 (95% CI: 1.16– 1.17)), non-western ethnicity (IRR=1.02 (95% CI: 1.01– 1.02)), living alone (IRR=1.08 (95% CI: 1.08– 1.09)), age groups ≥ 81 years (IRR=2.00 (95% CI: 1.98– 2.02)) and 0– 18 years (IRR=1.66 (95% CI: 1.66– 1.67)) and low income (IRR=1.41 (95% CI: 1.40– 1.42)) were more likely to contact OOH health care compared to males, Danish ethnicity, citizens cohabitating, age 31– 65 years and high income. Disability pensioners more often contacted OOH care (IRR=1.79 (95% CI: 1.77– 1.81) compared to employees. Old age (≥ 81 years) (OR=3.21 (95% CI: 3.13– 3.30)), receiving cash benefits (OR=2.45 (95% CI: 2.36– 2.54)), low income (OR=1.76 (95% CI: 1.72– 1.81)) and living alone (OR=1.40 (95% CI: 1.37– 1.42)) were all associated with EMS contacts rather than OOH-PC contacts.Conclusion: Several sociodemographic factors were associated with contacting a health care service outside office hours and with contacting EMS rather than OOH-PC. Old age, low income, low education and low socioeconomic status were of greatest importance.Keywords: out-of-hours health care, delivery of health care, Denmark, telephone hotline, telephone triage